2019
DOI: 10.1001/jamanetworkopen.2019.2606
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pharmacy Closures and Adherence to Cardiovascular Medications Among Older US Adults

Abstract: Key Points Question What is the association between pharmacy closures and adherence to cardiovascular medications among US adults 50 years or older? Findings Among 3.1 million individuals in this national cohort study, older adults filling statins, β-blockers, or oral anticoagulants at pharmacies that closed experienced an immediate statistically and clinically significant decline in adherence during the first 3 months after closure compared with their coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…In 2018, 16% of rural independent pharmacies had closed during the previous 16 years (3). Community pharmacies dispense 90% of medications in the United States (4), and pharmacy closures create disruptions in medication access that negatively affect medication adherence (5). Decreasing adherence rates lead to greater disease progression and create a substantial financial burden on the health care system (6).…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, 16% of rural independent pharmacies had closed during the previous 16 years (3). Community pharmacies dispense 90% of medications in the United States (4), and pharmacy closures create disruptions in medication access that negatively affect medication adherence (5). Decreasing adherence rates lead to greater disease progression and create a substantial financial burden on the health care system (6).…”
Section: Introductionmentioning
confidence: 99%
“…Among participants in the California Health Interview Survey, diabetes patients living in unsafe neighborhoods were more likely to delay filling medications (OR = 1.69, 95% CI: 1.19 to 2.40) [19]. A recent study by Qato et al (2019) reported a significant reduction in adherence to cardiometabolic medications among patients living in low-income neighborhoods with fewer pharmacies (−7.98%; 95% CI, −8.50% to −7.47%) compared with their counterparts [20]. These data, together with ours, provide evidence that the social, economic and the built environments of residential locations are potentially influential in how populations might adhere to treatment with medications.…”
Section: Discussionmentioning
confidence: 98%
“…Nationally representative data from Medicare and commercial health plan beneficiaries in the U.S. showed that adherence to AHM as well as antidiabetic and antilipid medications varied by geographic regions [16]. A few studies, all focusing on oral antidiabetic medications, reported that medication adherence is inversely associated with neighborhood social affluence, residential stability, socioeconomic advantage and safety [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…So it is clear that the margins on prescriptions in most community pharmacies are razor‐thin and that the reimbursement models imposed by the various payers are incredibly complex. The lack of a viable financial and business model for community pharmacies has prompted a rash of recent community pharmacy closures (both chain and independent) and it has been recently found that these closures decrease adherence and impact health . Importantly, there is no payment for the pharmacist's cognitive services, and one could argue that this is why so little is done in this regard for patients.…”
Section: Dilemma Of Pharmacy Payment Structuresmentioning
confidence: 99%